2021
DOI: 10.3390/foods10112706
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa Coproducts-Based and Walnut Oil Gelled Emulsion as Animal Fat Replacer and Healthy Bioactive Source in Beef Burgers

Abstract: The aim of this work was to evaluate the effects on the chemical, physic-chemical, technological, and sensory properties of beef burger when replacing different quantities of fat (50 and 100%) with different levels of oil-in-water-gelled emulsion elaborated with walnut oil and cocoa bean shell flour (GECW). The chemical composition of the samples was affected by the fat replacement. The reformulation increased the moisture and ash content while the fat and protein content decreased with respect to the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 48 publications
10
21
2
Order By: Relevance
“…These results reflected the low oil proportion used in the hydrogels (37.2%). Concerning fat reduction, the present study accords with other studies in which animal fats were totally or partially replaced with various healthy oils, such as walnut oil [ 28 ], tiger nut oil [ 5 , 40 ], avocado or pumpkin seed oils with algal oil [ 7 ], chia, tiger nut and linseed oils [ 11 , 21 ], canola oil [ 9 , 29 , 65 ], olive oil [ 63 ], algal oil [ 12 ] and a mixture of wheat germ and algal oils [ 23 ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…These results reflected the low oil proportion used in the hydrogels (37.2%). Concerning fat reduction, the present study accords with other studies in which animal fats were totally or partially replaced with various healthy oils, such as walnut oil [ 28 ], tiger nut oil [ 5 , 40 ], avocado or pumpkin seed oils with algal oil [ 7 ], chia, tiger nut and linseed oils [ 11 , 21 ], canola oil [ 9 , 29 , 65 ], olive oil [ 63 ], algal oil [ 12 ] and a mixture of wheat germ and algal oils [ 23 ].…”
Section: Resultssupporting
confidence: 90%
“…Overall, the T2 sample still has the highest PUFA content compared to the control group. These results are consistent with the literature, in which several other authors reported that the reformulation of meat products with vegetable and/or marine oil hydrogels causes a significant increase in unsaturated fatty acid contents [5,7,23,28,29,70,71]. As mentioned before, marine oils contain high amounts of n-3 fatty acids [12] and the results obtained in the present study can confirm this.…”
Section: Fatty Acidssupporting
confidence: 94%
See 3 more Smart Citations